1986
DOI: 10.7863/jum.1986.5.11.647
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal endometrial fluid collections: always an indicator of malignancy?

Abstract: An endometrial collection in a postmenopausal woman is abnormal. Its potential for heralding pelvic malignancy has been emphasized. Although malignancy must always be excluded, the authors' experience with a large outpatient population indicates that benign causes of uterine fluid collections may be more common than previously reported. During a 14-month period eight postmenopausal women with endometrial fluid collections were identified in the outpatient ultrasound department of the Massachusetts General Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
5

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 2 publications
0
6
0
5
Order By: Relevance
“…The significance of intrauterine fluid collection and cervical stenosis was investigated in previous studies with conflicting results; Breckenridge et al [6] investigated women with uterine fluid collection and found malignancy in 16 of 17 such patients, 11 of which had cervical stenosis and the final diagnosis was carcinoma of the uterine corpus or cervix. McCarthy et al [7] reported tow malignancies out of eight patients with asymptomatic intra uterine fluid collection. On the other hand, In a recent prospective study by Debby et al [8]; 82 postmenopausal women with cervical stenosis and endometrial fluid collection were investigated by curettage or hysteroscopy; no patient was found to have an underlying malignancy, 84 percent had an atrophic endometrium and one patient was diagnosed with a complex hyperplasia with atypia of the endometrium, moreover the incidence of intrauterine pathology increased with the increasing thickness of the endometrium as observed in ultrasound with all patients with endometrial thickness less than 3 mm (Two endometrial layers excluding the uterine fluid) had atrophic endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of intrauterine fluid collection and cervical stenosis was investigated in previous studies with conflicting results; Breckenridge et al [6] investigated women with uterine fluid collection and found malignancy in 16 of 17 such patients, 11 of which had cervical stenosis and the final diagnosis was carcinoma of the uterine corpus or cervix. McCarthy et al [7] reported tow malignancies out of eight patients with asymptomatic intra uterine fluid collection. On the other hand, In a recent prospective study by Debby et al [8]; 82 postmenopausal women with cervical stenosis and endometrial fluid collection were investigated by curettage or hysteroscopy; no patient was found to have an underlying malignancy, 84 percent had an atrophic endometrium and one patient was diagnosed with a complex hyperplasia with atypia of the endometrium, moreover the incidence of intrauterine pathology increased with the increasing thickness of the endometrium as observed in ultrasound with all patients with endometrial thickness less than 3 mm (Two endometrial layers excluding the uterine fluid) had atrophic endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The data in the reports arc conflicting: while Breckenridge et al [2] reported that 16 of 17 postmenopausal women with endometrial fluid col lections had gynecologic cancer, McCarthy et al [4] only identified 2 cases of cancer out of 8 postmenopausal wom en with fluid collection. In a condition frequently encoun tered in menopause, the uterus is obstructed by cervical stenosis and may fill with fluid; it can have a noncancerous etiology such as infection and postmenopausal hor mone replacement therapy [5].…”
Section: Discussionmentioning
confidence: 74%
“…Many studies have shown that endometrial thickness is a reliable indicator of uterine pathology (1)(2). In some earlier studies it has been reported that intracavitary fluid is a sign of gynecological cancer, especially cervical or uterine cancer (3)(4)(5)(6)(7)(8)(9). Several earlier studies in postmenopausal women have shown a thickened endometrium and a tumor to be a sign of pathology in conjunction with uterine fluid.…”
mentioning
confidence: 99%